Ketone Bodies as Ergogenic Aids in Endurance Sports: Biochemical Mechanisms, Supplementation Protocols, and Performance Outcomes — A Literature Review - Garbaciak, Jędrzej; Śmigielski, Michał; Czarny, Norbert; Dzitkowska, Kinga; Broniecka, Anna; Figwer, Krzysztof; Figwer, Agnieszka; Karbownik, Liwia; Kolasa, Magdalena; Kasterka, Milena (Quality in Sport, 2026)
Ketone bodies — principally β-hydroxybutyrate (β-HB) and acetoacetate (AcAc) — are endogenous metabolites that serve as alternative fuel substrates during states of reduced carbohydrate availability. Advances in the synthesis of ketone esters (KE) and ketone salts (KS) have enabled the acute elevation of circulating ketones independent of dietary restriction, creating promising ergogenic opportunities. Ketone esters acutely raise blood β-HB to one-digit millimolar concentrations within 30–60 minutes and can shift substrate utilization toward ketone and fat oxidation, sparing muscle glycogen and lowering blood lactate during submaximal exercise; ketone salts produce substantially lower ketosis and weaker effects. The evidence on acute endurance performance is inconsistent: a single influential trial reported a small benefit when a ketone monoester was co-ingested with carbohydrate, but this has not been reliably reproduced, and other controlled trials report neutral or impaired performance, particularly with the less palatable acetoacetate diester and with ketone salts at higher intensities. A more consistent signal has emerged in the recovery and adaptation domain, where ketone ester ingestion has been associated with enhanced post-exercise muscle glycogen synthesis and attenuated overreaching during intensified training. Overall, exogenous ketones are a biochemically plausible but unproven ergogenic strategy for acute endurance performance, with their most defensible current application lying in recovery; the heterogeneity of findings reflects differences in supplementation form, dose, timing, co-ingested macronutrients, training status, and exercise modality. Controlled trials with individualized protocols are needed before definitive recommendations may be established. This literature review evaluates the current evidence on the biochemical mechanisms, supplementation protocols, and effects of exogenous ketone body administration on endurance sport performance.